The gender composition of corporate boards and firm performance : Evidence from Russia - Garanina, Tatiana; Muravyev, Alexander (Elsevier, 2020)
This paper studies economic effects of the gender composition of corporate boards, employing a novel longitudinal dataset of publicly traded Russian companies over 1998–2014. Using multiple identification approaches, alternative measures of gender diversity, and several performance indicators, we find some evidence that companies with gender-diverse boards have higher market values and better profitability. These effects are particularly pronounced when firms appoint several women directors, which is consistent with the critical mass theory. The effects appear to be stronger in bad economic times. Overall, we find some support to “the business case” for more women on corporate boards.
Keywords: Board of directors; Gender diversity; Firm performance; Russia; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|